Zolpidem dependence in an adult with bipolar affective disorder and epilepsy: A case report - Sujita Kumar Kar; Suyash Dwivedi (General Psychiatry)
Zolpidem is a short-acting non-benzodiazepine hypnotic agent, commonly recommended for short-term treatment of insomnia. Zolpidem has less dependence potential than benzodiazepines. Patients with mental illnesses often have disturbed sleep, for which zolpidem is often prescribed. Long-term use and self-medication (in more than recommended doses) are more likely to cause dependence. We report here a case of bipolar affective disorder with epilepsy, who developed dependence to zolpidem and had severe withdrawal symptoms. The management issues are also discussed with review of the literature.